Minimization of Losses in Converter-Fed Induction Motors – Optimal Flux Solution - Pires, Waldiberto de Lima; Mello, Hugo Gustavo Gomez; Nau, Sebastião Lauro; Sobrinho, Alexandre Postól (IntechOpen, 2011)
None